Effects of change in dysfunctional beliefs in avatar-based cognitive therapy for depressive symptoms: a randomized parallel trial - Nicolina Laura Peperkorn; Julia Ohse; Janosch Fox; Merle Kuhlencord; Christin Janine Grevenhaus; Joshua Krutzki; Michael Witthöft; Youssef Shiban (Scientific Reports)
Abstract This study evaluated the effect of an avatar-based intervention on depressive symptoms and self-esteem. Participants (N = 151) with subclinical depressive symptoms were instructed to challenge an avatar over three sessions. While participants within the intervention group challenged their personal dysfunctional beliefs, participants in the control group challenged nonsense statements. Allocation to treatment groups was randomized. Data collection took place pre-intervention and post-intervention. Statistical analysis revealed a significant decrease in depressive symptoms, which was more pronounced for the intervention group (p < .01), as well as a significant group × time interaction for self-esteem (p < .05). The effect on depression symptom strength was large in the experimental group (d = − 1.19) and medium (d = − 0.72) in the control group, while the effect on self-esteem was moderate (d = 0.54) in the intervention and small (d = 0.29) in the control group. Our findings on symptom reduction align with prior research, while positive effects on self-esteem are a novelty. These results demonstrate the intervention’s potential for reducing the symptoms of mental illness.